PENGARUH PENGGUNAAN TIGA JENIS KUNING TELUR DALAM PENGENCER AIR KELAPA MUDA TERHADAP KUALITAS SEMEN SAPI BALI (Impact of Adding Three Different Egg Yolks to Young Coconut Water Diluent on Bali Cattle Semen Quality) - Ulu, Krista Florida; Belli, Henderiana L.L; Riwu, Agustinus R.; Hine, Thomas M. (JURNAL NUKLEUS PETERNAKAN, 2024)
Young coconut water (CW) can be used as a diluent which can provide nutrients and other protective substances for the life of spermatozoa. Egg yolk is one of the important components in semen diluent, because it has a very important role in protecting the plasma membrane and acrosome during storage. The aim of this research was to determine the best type of egg yolk in combination with young coconut water to maintain liquid semen quality of Bali cattle. This research used a complete random design consisting of 6 treatments and 5 replications. The basal diluent in all treatments was 80 percent of CW combined with 20 percent chicken egg yolk (C), duck egg yolk (D), quail egg yolk (Q). The treatments in question are P0= CW-C, P1= CW-D, P2= CW-PQ, P3= CW-CD, P4= CW-CQ, and P5= CW-CDQ. Data were analyzed using one-way ANOVA and Duncan tests. Until the 6th day of storage, the P3 treatment produced higher semen quality than the control (P<0.05) except that the sperm abnormality variable showed no significant difference (P>0.05). On the other hand, treatment P3 showed no significant difference from treatments P1, P2, P4, and P5 (P>0.05). The quality of Bali cattle semen up to the sixth day of storage in treatment P3 was: 42.00%. 48.76%, 5.71%, 6.2 days respectively for the variables motility, viability, abnormalities and sperm survival. The results of this study concluded that a combination of chicken and duck egg yolks added to coconut water is the best diluent that can maintain the quality of Bali cattle sperm.